Building Moral Character in Students Learning Citizenship Education - Cindi Khairani Br Purba (International Journal of Students Education, 2024)
Citizenship education has an important role in building students' moral character. This research aims to explore effective strategies and methods in forming moral character, including values such as integrity, empathy and social responsibility. By combining a holistic curriculum approach and student-centered learning practices, citizenship education can provide opportunities for students to develop a deep understanding of moral values and how to apply them in everyday life. The results of this research can provide guidance for educators in designing citizenship education programs that are effective in building students' moral character. The conclusion of this research is that citizenship education can be an effective forum for strengthening moral values such as integrity, empathy and social responsibility.